Status and factors influencing access of extension and advisory services on forage production in Kenya - Gatheru, M.; Njarui, D.M.G.; Gichangi, Elias M.; Ndubi, J.M.; Murage, A.W.; Gichangi, Anne W (Sciencedomain International, 2021)
This study assessed the status and factors influencing access of extension and advisory services (EAS) for forage production among smallholder dairy farmers in Kenya. Using a multistage stratified random sampling, data were collected from 316 and 313 farmers in Kangundo sub-County and Kirinyaga Counties of Kenya, respectively. The intensity of dairy farming formed the basis of selection of the study areas. The data were analysed using descriptive statistics and binary logistic regression model. Results indicated that, overall the proportion of farmers who accessed EAS on forage production in Kirinyaga (26.4%) was double that of Kangundo (13.6%). Government was the main provider of EAS on forage production and accounted for between 73 to 90% of services in Kangundo and 54 to 81% in Kirinyaga. The main channels for accessing EAS in both sites were trainings (29 - 31%) and field days (22 - 30%). Overall, majority of farmers (71 - 73%) were satisfied with the information and services they received on forage production. The empirical estimates of logistic regression revealed that the probability of access to EAS increased with access to credit, membership to farmer groups and importance of livestock on household’s food security. We recommend that the governments use innovative extension approaches and strengthen formation of farmer groups/organizations in order to improve access of EAS by smallholder dairy farmers for enhanced forage production.